Phenomenology yesterday, today, and tomorrow: a proposed phenomenological response to the double challenges of contemporary recovery-oriented person-centered mental health care - Messas, Guilherme; Stanghellini, Giovanni; Fulford, K. W. M. (Bill) (Frontiers in Psychology, 2023)
This paper argues that a dialectical synthesis of phenomenology's traditional twin roles in psychiatry (one science-centred, the other individual-centred) is needed to support the recovery-oriented practice that is at the heart of contemporary person-centred mental health care. The paper is in two main sections. Section I illustrates the different ways in which phenomenology's two roles have played out over three significant periods of the history of phenomenology in 20th century psychiatry: with the introduction of phenomenology in Karl Jaspers' General Psychopathology in 1913; with the development a few years later of structural phenomenological psychopathology; and in the period of post-War humanism. Section II is concerned with the role of phenomenology in contemporary mental health. There has been a turn to phenomenology in the current period, we argue, in response to what amounts to an uncoupling of academic psychiatry from front-line clinical care. Corresponding with the two roles of phenomenology, this uncoupling has both scientific aspects and clinical aspects. The latter, we suggest, is most fully expressed in a new model of 'recovery', defined, not by the values of professionals as experts-by-training, but by the values of patients and carers as experts-by-experience, specifically, by what is important to the quality of life of the individual concerned in the situation in question. We illustrate the